The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1088/0031-8949/48/2/001
|View full text |Cite
|
Sign up to set email alerts
|

EinsteinA-coefficients for transitions among the 3s23p3states of S II

Abstract: S I1 Einstein A-coefficientsEinstein A-coefficients for transitions among the 3s23p3 states of SII, calculated with the CIV3 code, are found to be up to -25% different from those of Mendoza and Zeippen. These new results are used to derive the theoretical emission line ratio R = 1(3s23p3 4S;iz-3s23p3 2D:/2)/ I(3s23p3 4S;/2-3s23p3 2D;/z) = I(6717 A)/1(6730A), which is a very useful electron density diagnostic for gaseous nebulae. The present diagnostin are up to 10% larger than those deduced using the A-values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Using the double-beam spectrograph mounted on the ANU 2.3 m telescope, Kingsburgh & English (1992) ple of Galactic PNe and found that electron densities derived from the two ratios were in excellent agreement. On the other hand, a very different result was obtained by Meatheringham & Dopita (1991) Aller et al 1996;Feibelman et al 1994Feibelman et al , 1996Hyung 1994;Hyung & Aller 1995a,b, 1996, 1997a,b, 1998Hyung et al 1993Hyung et al , 1994aHyung et al ,b,c, 1995Hyung et al , 1997Hyung et al , 1999aHyung et al ,b, 2000Hyung et al , 2001Keyes et al 1990;Keenan et al 1993Keenan et al , 1996Keenan et al , 1997 they determined simultaneously electron densities and temperatures using a number of plasma diagnostic lines in the optical and ultraviolet and found that overall the data yielded compatible and consistent results. More recently, Copetti & Writzl (2002), using data published in the literature, compared the observed line ratios for a number of density-diagnostics, instead of densities deduced from them, thus avoiding discarding measurements that yield ratios close to or beyond the the low-or high-N e limits.…”
Section: Introductionmentioning
confidence: 90%
“…Using the double-beam spectrograph mounted on the ANU 2.3 m telescope, Kingsburgh & English (1992) ple of Galactic PNe and found that electron densities derived from the two ratios were in excellent agreement. On the other hand, a very different result was obtained by Meatheringham & Dopita (1991) Aller et al 1996;Feibelman et al 1994Feibelman et al , 1996Hyung 1994;Hyung & Aller 1995a,b, 1996, 1997a,b, 1998Hyung et al 1993Hyung et al , 1994aHyung et al ,b,c, 1995Hyung et al , 1997Hyung et al , 1999aHyung et al ,b, 2000Hyung et al , 2001Keyes et al 1990;Keenan et al 1993Keenan et al , 1996Keenan et al , 1997 they determined simultaneously electron densities and temperatures using a number of plasma diagnostic lines in the optical and ultraviolet and found that overall the data yielded compatible and consistent results. More recently, Copetti & Writzl (2002), using data published in the literature, compared the observed line ratios for a number of density-diagnostics, instead of densities deduced from them, thus avoiding discarding measurements that yield ratios close to or beyond the the low-or high-N e limits.…”
Section: Introductionmentioning
confidence: 90%
“…Hibbert and co-workers have shown that two-electron promotions are important to include to get accurate energies, f -values and Einstein coefficients [63,64] 2 of the residual sulfur singly ionized ion were included in the close-coupling expansion. PI cross section calculations with this 512-level model were performed in the Dirac Coulomb approximation using the recently developed parallel version of the DARC codes [57,58].…”
Section: A Dirac-coulomb R-matrixmentioning
confidence: 99%
“…Hibbert and co-workers have shown that two-electron promotions are important to include to get accurate energies, f -values and Einstein coefficients (Ohja & Hibbert 1987;Keenan et al 1993) which are included in the present study. In our photoionisation cross-section calculations for this element, all 512 levels arising from the eight configurations: 3s 2 3p 3 , 3s3p 4 , 3s 2 3p 2 3d, 3s 2 3p3d 2 , 3s3p 3 3d, 3p 3 3d 2 , 3p 5 , 3s3p 2 3d 2 of the residual chlorine doubly ionized ion were included in the close-coupling expansion.…”
Section: Photoionisationmentioning
confidence: 99%